High density lipoproteins and atherosclerosis: Emerging aspects - Sala, F.; Catapano, A.; Norata, Giuseppe (Chinese P L A General Hospital * Institute of Geriatric Cardiology, 2012)
High density lipoproteins (HDL) promote the efflux of excess cholesterol from peripheral tissues to the liver for excretion. This ability is responsible for the most relevant antiatherogenic effect of HDL. The ability of HDL to promote cholesterol efflux results also in the modulation of a series of responses in the immune cells involved in atherosclerosis, including monocyte-macrophages, B and T lymphocytes. Furthermore, during inflammation, the composition of this class of lipoproteins varies to a large extent, thus promoting the formation of dysfunctional HDL. The aim of this review is to discuss the emerging role of HDL in modulating the activity of immune cells and immune-inflammatory mediators during atherogenesis. © 2012 JGC All rights reserved.